Secure Online Data Sharing in Cloud by Private Transmit Cryptosystem Using Aggregate Keys - Amarnath Reddy, E; Srinuvasa Reddy, M; Manisha, Kompally; Mamatha, B (International Journal of Engineering and Technology, 2018)
Cloud has become a crucial part of our day to day life because of its easy, effortless and straightforward nature of data storing and sharing. One of the important concerns for many users is data storing, we mustn’t forget about data sharing. A convenient way of online data sharing is to look at its pros for simple access while preserving security are cons for any user. Thus, a better way of ensuring user’s data is to implement data integrity with the KAC scheme. This scheme provides an efficient sharing method of decrypting multiple sets of data with the single key. It’s one among many ways of quick and effective data retrieval in case of data loss or data alteration on the cloud. It also uses the broadcast algorithm to distribute data for a specific set of users. This scheme uses basic HMAC, one of the secure hash functions for the stability of data integrity.  Therefore provides a protected environment where a user can share the bulk of data through integrity. Another advantage of using this scheme could reduce the burden of computation over the cloud.